Ethics in Zoroastrianism, from MinuyeXerad’s Perspective - Mostafa Farhoodi (اخلاق وحیانی, 2013)
Ethics in Zoroastrianism has a strong bond with the nature of existence. In Zoroastrian religion, Ahura Mazda’s absolute authority in the world and the salvation of mankind is dependent upon mankind’s ethical life. Accordingly, this ideal must be realized in different aspects of human life by the observance of all that is considered as beliefs, rituals and rites. Human beings, in whatever position and rank they may be, must try at their full capacity, while observing ethics, to house AmeshaSpenta in themselves and to purify the world which has been contaminated by the Demon (Ahriman) and to annihilate the Demon. Having a sound heart accompanied by a faith based on an immense knowledge is to be treasured much more than the outward behavior. Human beings can pave the way for their moral development by seeking assistance with wisdom that is accompanied by freewill. It is noteworthy that the Demon can be a serious obstacle to human beings’ achieving perfection by damaging their wisdom and the destiny that is decided for them.